Analisis Keabsahan Akta Di Bawah Tangan Atas Jual Beli Tanah yang Mengandung Cacat Kehendak Serta Penerapan Kriteria Pembeli Beritikad Baik (Studi Putusan Nomor 18/Pdt.G/2021/Pn Wtp) - Ajo, Fransiska Litania Ea Tawa; Djajaputra, Gunawan (UNES Law Review, 2023)
The purpose of writing this article is to find out the validity of buying and selling land under the hands and also to understand the criteria for buyers in good faith. The basis of this research is Decision Number 18/Pdt.G/2021/PN Wtp. This writing uses normative juridical research methods. Based on the analysis and looking at the court decision, it is known that the sale and purchase carried out is invalid because the land is inherited land that has not been divided, but the seller who is the heir sells the land without the knowledge of the other heirs so that the sale and purchase contains a defect in the will because it is not based on an agreement. together. However, the sale and purchase was also based on deception carried out by the seller against the buyer (Defendant) where the buyer was not aware of any defects in the sale and purchase. Based on this, the buyer should be said to be a buyer in good faith, but even so, the buyer is obliged to objectively examine the ownership of the land.